Application of multi-core encapsulated Michelia alba D.C. flavor powder in Thai steamed dessert (Nam Dok Mai) - Rajnibhas Samakradhamrongthai (2018)
© 2017, Chiang Mai University. All rights reserved. This research aimed to investigate the suitable content of flavor encapsulated powder for controlled release and its flavor release model. The Nam Dok Mai (NDM) dessert was selected for this experiment due to the high moisture content and high temperature during its heating process. The controlled release of the aroma and flavor of the multi-core encapsulated Michelia alba D.C. (MAD) flavor powder was used in this experiment. The variations of the multi-core encapsulated MAD flavor powder (MEFP) used in this research were 0, 0.5, 1, 3, and 5% w/w. The color and texture profiles were analyzed, together with sensory evaluation. The Pandan flavor release was examined from the outer shell of the MEFP, whereas the MAD aroma release was examined from the inner core. The results revealed that the NDM dessert containing 1% w/w of the MEFP demonstrated the most preferable of the sensory preferences. The consumer acceptance of the NDM dessert with 1% w/w of the MEFP showed that the NDM dessert provided a 9-point hedonic scale sensory rating score in range of 6.0-6.3. The acceptance and purchase intention were also revealed high percentages as 98.0% and 98.3%, respectively. The controlled release model for the NDM dessert using the time-intensity method revealed the maximum intensity of the Pandan flavor and the White Champaca flavor at 48.79 and 50.80, respectively within 9thsec. This indicated that the White Champaca flavor provided higher intensity than the Pandan flavor in the NDM dessert.